A Clinical Study on Denture Stomatitis in a Group of Denture Wearers in Sulaimani Governorate - Karim, Jwan F. A.; A.Kareem, Saeed A.Latteef (Sulaimani Journal for Pure and Applied Sciences, 2007)
Denture stomatitis is the most common condition which affects the palatal mucosa in 50% of wearers of complete or partial removable dentures. The etiology of denture stomatitis is multicausal, a wide range of both local and systemic predisposing conditions maybe involved in its pathogenesis, The present study involved a clinical survey on the-most predisposing local factors among 40 patients (18 male, 22 female) in the ,development of denture stomatitis within denture wearers attended Prosthodontics clinic of the College in Sulaimani Governorate Their age ranged from 45- 75 years. The study showed that denture stomatitis of pinpoint hyperplasia occurred in %30 of the cases, diffuse erythema found in 55% and inflammatory papillary hyperplasia in %15. We observed that most of these cases were caused by chronic infection by candida albicans associated with mechanical injury due to wearing dentures day and night constantly arnang (%74.2) of cases and (25.7%) in those wearing their dentures during the day only. It is concluded that in order to prevent or minimize the extent of these lesions, denture wearers are advised to clean their mouth and dentures regularly, to wear their dentures during day time only and should be recalled for examination of the oral cavity and their dentures.
Keywords: Candida; Denture; Stomatitis